2006
DOI: 10.2320/matertrans.47.1332
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Double Tempered 8%Cr-2%WVTa Martensitic Steel

Abstract: Creep testing was carried out at around 650 C for a martensitic 8Cr-2WVTa steel (F82H), which is a candidate alloy for the first wall of the fusion reactors of the Tokamak type. Rupture strength of the double tempered steel (F82HD) is lightly higher than that of simply tempered steel (F82HS). On the other hand, creep rate of F82HD is obviously smaller than that of F82HS in acceleration creep, though creep strain of F82HD in transition creep, where creep rate decreases with increasing strain, is larger than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…4), but the apparent lattice strain and the apparent crystalline particle size (Fig. 5) change discontinuously with crest and trough between about 3 to 9 h. Referring the EBSP measurements reported in the literature 15,27) it is found from the Figs. 4 and 5 that with the progress of tempering the re-distribution of the crystalline particles or the generation of subgrains may occur, which causes a local increase in internal stress and, as a consequence, the apparent lattice strain, and finally the rotation of the preferred orientation should take place.…”
Section: Discontinuous Changes In Tempering Curvessupporting
confidence: 58%
See 1 more Smart Citation
“…4), but the apparent lattice strain and the apparent crystalline particle size (Fig. 5) change discontinuously with crest and trough between about 3 to 9 h. Referring the EBSP measurements reported in the literature 15,27) it is found from the Figs. 4 and 5 that with the progress of tempering the re-distribution of the crystalline particles or the generation of subgrains may occur, which causes a local increase in internal stress and, as a consequence, the apparent lattice strain, and finally the rotation of the preferred orientation should take place.…”
Section: Discontinuous Changes In Tempering Curvessupporting
confidence: 58%
“…5 that both the apparent lattice strain and the apparent crystalline particle size vary largely from 2 to 12 h. Similar drastic changes among specific intensity, apparent lattice strain and apparent crystalline particle size during tempering or creep deformation of some martensitic steels are reported elsewhere. 10,15,27) In the literatures, electron back scattered pattern (EBSP) measurements were also reported along with the isothermal hardness curves, and the discontinuous changes in X-ray peaks of bulk specimens as shown in Figs. 4 and 5 were explained as follows: in case of the generation and/or growth of new subgrains through the recovery process of lath martensite structure, discontinuous changes in the preferred orientation takes place and, as a consequence, the generation of ultra fine grains around the block of martensite or subgrains should occur, which leads to the discontinuous changes in the local lattice strain and the average crystalline particle size as shown in Figs.…”
Section: X-ray Diffraction Of Bulk Specimensmentioning
confidence: 99%
“…5 instead of the black regions. Tamura et al 22) recently confirmed the existence of the ultra fine grains in crept specimens of a similar steel using the same experimental conditions. They also confirmed that TEM contrast corresponding to the ultra fine grains was not observed.…”
Section: Recovery Processmentioning
confidence: 72%
“…5 are observed in a crept specimen of a similar martensitic steel. 22) The grain tolerance angle defines a grain by specifying the minimum misorientation value that was caused by a grain boundary. Measurements with misorientations below this value are grouped together to difine a grain.…”
Section: Ebsp Measurementmentioning
confidence: 99%
“…[35] Further, they had also used it to describe the creep mechanism with parameters such as activation energy, activation volume, and mobile dislocation density. [36,37] Using these parameters, the equivalent obstacle spacing for mobile dislocations was calculated based on some assumptions. [36] The equivalent obstacle spacing calculated that was using creep curves was confirmed to be comparable with the interparticle distance or subgrain size that was observed using TEM.…”
Section: Introductionmentioning
confidence: 99%